Pemanfaatan Media Audio Visual Berbasis Sejarah Untuk Meningkatkan Kreativitas Peserta Didik Ditingkat SMA - Alqorana, Sifana; Syariffudin, Syariffudin; Pamulaan, Alif Bahtiar (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
History education designed by teachers should be able to help students understand historical events. To improve learners' abilities and enhance their historical thinking skills, teachers should combine contextual learning models with the use of film media. Media such as films can keep learners interested, increase their thoughts and input and enhance their fantasy power. To make learning more interesting, the use of additional media such as technology, audio-visual media, is essential. In constructivistic history learning, the use of audio-visual media has been applied in high schools. This research aims to find out the preparation, implementation, evaluation, and constraints in learning constructivistic history with audio-visual media in high school. In developing the effective use of audiovisual media to increase students' interest in history lessons, this study investigated the library that received history learning through audiovisual media. The results of this study show that audiovisual media can significantly develop students' interest in history lessons.